Search for ZZ resonances in the 2ℓ2ν final state in proton-proton collisions at 13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Nature, 2018)
A search for heavy resonances decaying to a pair of Z bosons is performed using data collected with the CMS detector at the LHC. Events are selected by requiring two oppositely charged leptons (electrons or muons), consistent with the decay of a Z boson, and large missing transverse momentum, which is interpreted as arising from the decay of a second Z boson to two neutrinos. The analysis uses data from proton-proton collisions at a center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 35.9 fb−1 . The hypothesis of a spin-2 bulk graviton (X) decaying to a pair of Z bosons is examined for 600 ≤ mX ≤ 2500 GeV and upper limits at 95% confidence level are set on the product of the production cross section and branching fraction of X → ZZ ranging from 100 to 4 fb. For bulk graviton models characterized by a curvature scale parameter ˜k = 0.5 in the extra dimension, the region mX < 800 GeV is excluded, providing the most stringent limit reported to date. Variations of the model considering the possibility of a wide resonance produced exclusively via gluon-gluon fusion or q¯q annihilation are also examined